Interlaboratory Application of Raman CO2 Densimeter Equations: Experimental Procedure and Statistical Analysis Using Bootstrapped Confidence Intervals. Issue 7 (July 2021) - Remigi, Samantha; Mancini, Tullio; Ferrando, Simona; Frezzotti, Maria Luce
Raman spectroscopy has been used extensively to calculate CO2 fluid density in many geological environments, based on the measurement of the Fermi diad split (Δ; cm –1 ) in the CO2 spectrum. While recent research has allowed the calibration of several Raman CO2 densimeters, there is a limit to the interlaboratory application of published equations. These calculate two classes of density values for the same measured Δ, with a deviation of 0.09 ± 0.02 g/cm 3 on average. To elucidate the influence of experimental parameters on the calibration of Raman CO2 densimeters, we propose a bottom-up approach beginning with the calibration of a new equation, to evaluate a possible instrument-dependent variability induced by experimental conditions. Then, we develop bootstrapped confidence intervals for density estimate of existing equations to move the statistical analysis from a sample-specific to a population level. We find that Raman densimeter equations calibrated based on spectra acquired with similar spectral resolution calculate CO2 density values lying within standard errors of equations and are suitable for the interlaboratory application. The statistical analysis confirms that equations calibrated at similar spectral resolution calculate CO2 densities equivalent at 95% confidence, and each Raman densimeter does have a limit of applicability, statistically defined by a minimum Δ value, below which the error in calculated CO2 densities is too high. Graphical Abstract